2010
DOI: 10.1007/s15010-009-9249-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of a Saquinavir-Containing Antiretroviral Regimen in Previously ART-Naïve or Pretreated but Protease Inhibitor-Naïve HIV-Positive Patients

Abstract: The results of this observational cohort study of treatment with the 500-mg tablet formulation of SQV are consistent with high efficacy and tolerability results seen in controlled studies of SQV/r. This analysis confirms that SQV/r is effective and well tolerated in ART-naïve and pretreated but PI-naïve patients in 'real-world' clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
3
1
1
Order By: Relevance
“…The efficacy of SQV/r 1000/100 mg bid in treatment-naïve patients using the 500 mg film-coated formulation of SQV up to 48 weeks has been reported previously in the clinical trial setting [8], and confirmed by similar findings in our 48 week analysis of patients treated in routine clinical practice in the RAINBOW cohort [10]. The 96 week data presented here extend and support evidence of efficacy and safety of SQV/r in 'real world' settings.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The efficacy of SQV/r 1000/100 mg bid in treatment-naïve patients using the 500 mg film-coated formulation of SQV up to 48 weeks has been reported previously in the clinical trial setting [8], and confirmed by similar findings in our 48 week analysis of patients treated in routine clinical practice in the RAINBOW cohort [10]. The 96 week data presented here extend and support evidence of efficacy and safety of SQV/r in 'real world' settings.…”
Section: Discussionsupporting
confidence: 88%
“…Treatment with SQV/r was well tolerated up to one line 96 weeks, with only seven patients in the total cohort (2.5%) withdrawing from treatment due to side effect issues, confirming the low incidence reported at 48 weeks [8,10]. The incidence and nature of AEs were similar in both ART-naïve and pretreated but PI-naïve patients, and were similar to those previously reported (most commonly gastrointestinal and diarrhea).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations